APLIKASI E-PROCUREMENT DALAM SISTEM INFORMASI MANAJEMEN PEMERINTAHAN DI UNIT PELAKSANA TEKNIS DAERAH (UPTD) LAYANAN PENGADAAN BARANG DAN JASA ELEKTRONIK (LPSE) KOTA PONTIANAK - Karina Oktriastra E.42009084 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
Procurement Application in Management Information Systems of Governance in District Technical Implementing Units Electronic Procurement Service. Script. Pontianak: Governments Science’s Program, Faculty of Social Politic Science Collaborate with West Borneo Province Government.E-procurement application in management information systems of Governance in UPTD. LPSE Pontianak experiencing problems such as lack of socialization, training and education for users, the disruption of website and lack of coordination among stakeholders in provision of infrastructure.The successfulness of e-procurement applications can be viewed through three important factors, Policy, People and Infrastructure. Which of the applications running in accordance with standard operating procedures, professional personnel resources and adequate infrastructure to optimize the passage of e-procurement in UPTD. LPSE Pontianak.To optimize the application of e-procurement, it is necessary to align the performance between government departments, then run the established standards, and ongoing development of a system in accordance with the required capacity to be able to realize the creation of good governance and clean government. Keywords: Application, Policy, People, Infrastructure, Good Governance and Clean Government